Analisis Beban Kerja Mental Mahasiswa Terhadap Sistem Perkuliahan Daring dengan Metode NASA-TLX - Desak Ayu Sista Dewi; A.A.I.A.S Komaladewi; Ferdiansyah Pratama Putra Setyawan (Dinasti Research, 2024)
The Covid-19 pandemic has posed a challenge to the use of technology in the education sector in Indonesia. This situation has made university students independent learners through online classes. In the beginning of Covid-19 the students at Udayana University have implemented online learning. In this context, students are required to understand the course material and complete assignments as part of learning evaluation, thus creating a distinct workload, including mental workload. To determine the extent of the students' mental workload, measurements were conducted using the NASA-TLX (National Aeronautics and Space Administration Task Load Index) method with 6 indicators. The measurement indicators were based on quantitative courses. This study involved 40 respondents who were students of the Industrial Engineering Study Program at Udayana University. The results showed that the mental workload on students was quite high, as evidenced by 23 out of 40 students in the synchronous method group and quantitative courses having a high WWL (Workload Weighting Level) classification. A high WWL classification was also shown in the asynchronous method group, with 26 students or 65%.